LAPORAN KASUS: KESEMBUHAN ENTERITIS HEMORAGIKA PADA ANAK ANJING KACANG YANG TERINFEKSI CANINE PARVOVIRUS - Purwitasari, Made Santi; Soma, I Gede; Batan, I Wayan (JURNAL KAJIAN VETERINER, 2022)
Canine parvovirus (CPV) is an infectious disease with clinical signs of bloody diarrhea (hemorrhagic enteritis) which is cause of death in infected dogs. A five-month-old female local dog with a weight of 4.3 kg, black and white coat on the ventral side came to the Rumah Sakit Hewan Pendidikan, Faculty of Veterinary Medicine, Udayana University with complaints of weakness, loss of appetite since the day before and vomiting in the morning of the examination. The dog is rescued and never been vaccinated before. Clinical examination showed weakness such as holding pain, pink pale eye mucosae, delayed skin turgor, Capillary Refill Time (CRT) more than two seconds, and increased respiratory rate. Dogs do not respond to handfeeding. On observation the dog experienced clear and foamy vomiting and foul-smelling bloody diarrhea. The native stool faecal examination showed negative results, while the CPV antigen rapid test examination showed positive results. Complete blood count showed that on the first day of hospitalization the dog had leukopenia, granulocytopenia, hyperchromic normocytic anemia and thrombocytopenia. The dog was diagnosed with CPV with a dubious prognosis. Dogs were given fluid therapy using sodium chloride 0.9% infusion and vitamin B complex, anti-emetic ondansetron, antibiotic cefotaxime, and vitamin K. Dogs were also treated with traditional medicine Fu Fang 1 mL and trigona honey 1 mL. Dogs are given a special feed Hills Prescription Diet A/D Urgent Care. The dog's condition improved after offering therapy for seven days and the dog was declared cured and could be sent home on the ninth day.